Throwing off the dark legacy when going down: Experience of status loss undermines reparation intentions prompted by narratives of the ingroup’s past wrongdoings - Waldzus, S.; Dumont, K.; Knoetze, L. (British Journal of Social Psychology, 2022)
Two experiments tested whether group members’ reparation intentions towards victims of the ingroup’s past wrongdoings depend on their experience of relative status change. We manipulated born-free White South Africans’ experience of accessibility of memories of past ingroup wrongdoings and their current experiences of status loss. For participants believing in the ingroup’s responsibility for past wrongdoing towards Black South Africans during Apartheid, status-loss experiences reduced reparation intentions prompted by the experience of memorizing examples of such wrongdoing as easy (Experiment 1, N = 193), and the ease to remember wrongdoing examples increased reparation intentions only if participants were reminded of status stability, but not if they were reminded of status loss (Experiment, N = 126). We conclude that the implications of narratives referring to past ingroup wrongdoings are contingent upon their relational function in ongoing social change processes. © 2021 British Psychological Society.